1996
DOI: 10.1016/s0741-5214(96)70077-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of death in nonruptured and ruptured abdominal aortic aneurysms

Abstract: Prolonged ventilation, perioperative myocardial infarction, a history of peripheral vascular disease, preoperative renal dysfunction, and a history of congestive heart failure are independent predictors of perioperative death in patients with nonruptured AAAs. For patients with ruptured AAAs, mortality rates can be estimated before surgery using age, level of consciousness, and cardiac arrest. For patients who survive the initial surgery for ruptured AAA, subsequent mortality rates can also be predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(90 citation statements)
references
References 25 publications
1
86
1
2
Order By: Relevance
“…17) Acute renal failure requiring hemodialysis has been reported to complicate the course of 0.5% to 2% of patients undergoing elective AAA repair, with associated in-hospital mortality ranging from 25% to 66%. 15,[18][19][20][21][22][23][24][25][26] Contrary to that report, our findings demonstrated that at 7 day after the operation, the incidence of a 10% or greater increase in serum Cr over the preoperative level was 10.9%, which was significantly lower in comparison to the previous report. Anatomical suitability for EVAR aortic neck diameter of 18-28 mm, neck length ≥15 mm, neck angulation <60, iliac diameter of 7.5-20 mm, length of iliac sealing zone ≥10 mm Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…17) Acute renal failure requiring hemodialysis has been reported to complicate the course of 0.5% to 2% of patients undergoing elective AAA repair, with associated in-hospital mortality ranging from 25% to 66%. 15,[18][19][20][21][22][23][24][25][26] Contrary to that report, our findings demonstrated that at 7 day after the operation, the incidence of a 10% or greater increase in serum Cr over the preoperative level was 10.9%, which was significantly lower in comparison to the previous report. Anatomical suitability for EVAR aortic neck diameter of 18-28 mm, neck length ≥15 mm, neck angulation <60, iliac diameter of 7.5-20 mm, length of iliac sealing zone ≥10 mm Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…The coding of complications in surgical patients was found to be valid, with a high positive predictive value [22]. In addition, we reviewed a random sample of 25 medical records from one hospital and found the coding of complications associated with in-hospital mortality to be 96% accurate [26], and complication rates are consistent with the literature [7,9,20]. We did not use a systematic scoring system such as APACHE II that requires a medical record review to adjust for severity of illness [21].…”
Section: Discussionsupporting
confidence: 60%
“…19,[29][30][31][32] Preoperative renal dysfunction is also associated with a poor outcome. [33][34][35] Liver Failure…”
Section: Acute Renal Failurementioning
confidence: 99%